Vuca World: the commitment of teacher organization and student outcome in Malaysian primary school - Abu, Abdul Rahim; Asimiran, Soaib; Abdullah, Arnida; Alias, Siti Noormi (Human Resources Management Academic Research Society (HRMARS), 2023)
Education is a process for individual development in the physical, emotional, spiritual, intellectual, and social aspects that can yield happiness, benefits, and progress in life for oneself, one nation, and religion. The primary-level formal education in Malaysia has two phases namely preschool and primary education is the foreground to the development and expansion of the students cognitive, affective, and psychomotor domains consistent with the National Education Philosophy (NEP). The sustainability of 21st-century education has emphasized a range of universal noble value-oriented practices. The mainstay of 21st-century learning is the United Nations Educational, Scientific and Cultural Organization (UNESCO) namely Intelligent Quotient (IQ) Emotional Quotient (EQ), and Spiritual Quotient (SQ), and they must be implemented in balance to fulfill the intention and goals of the NEP. That said, the world turmoil has spawned a volatile, vague even complex phenomenon. Whether it is realized or not, the VUCA crisis (volatility, uncertainty, complexity, ambiguity) has already lingered in the lives of the local community for the past two decades. The findings from past studies explained about the education sector experiencing a remarkable impact from the turmoil caused by VUCA. The challenge of holistic education has become greater owing to the unpredictability of the technological gap in forming the student outcome, especially for students in primary schools. This conceptual paper discusses the commitment of teacher organization and primary school student outcomes in the era of VUCA. Even though the direct relationship between the organization, the commitment of teacher organization, and students is not always easy, it is a significant indirect variable for student achievement. To ensure that our country can compete on the international stage, the quality of our education in this VUCA era needs to be given the main focus, especially at the primary level, involving various stages of implementers.